FEATURES OF HUMAN CAPITAL IN THE CONTEXT OF ECONOMIC SYSTEM EVOLUTION - Malynovska, Halyna; Ivasiv, Andriy; Bodnarchuk, Ihor; Danyleichuk, Ruslan (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article examines and substantiates the relationship between the development of human capital and the evolution of economic systems for the further development of recommendations for managing the development of human capital in modern conditions. The author proved the need for research aimed at establishing the peculiarities of the formation and development of human capital in the conditions of the evolution of economic systems. The result of such studies should be a theoretical substantiation of the role and place of human capital in the processes of evolutionary changes and confirmation of the priority of the impact on human capital for the effective development of the economic system. The author established that personal abilities in the structure of the primary human capital of the pre-industrial era are a personalized resource of knowledge, abilities, skills and experience that a person used to transform available natural and other resources into performance results in order to satisfy both personal and social needs. At the same time, in the era of industrial economy, the structure of human capital identified personalized intellectual resources (intellectual abilities of individuals who generate and justify ideas for technical, technological, organizational and other improvements), structural and market intellectual resources in the part of human knowledge about the possibilities of using the results intellectual activity and active intellectual resources as a result of the combination of man and machine. It was determined that changes in socio-economic formations are accompanied by changes in the component composition of the structure of human capital, which is formed in accordance with the conditions of development of economic systems. It is proposed to characterize the modern economic system by the term "intellectual-behavioral economy", taking into account the priority of the role of a person with his inherent intellectual and behavioral characteristics in the results of the economic activity of economic entities, and the implementation of human capital management functions in the conditions of such an economy requires the improvement of processes, procedures, decision-making technologies regarding organization, motivation, control and planning of its development, the results of which will determine the level of intellectualization of economic activity.